Edith Stein and Roman Ingarden –Concepts of Man - Stróżewski, Władysław (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2016)
In this article the author reconstructs and compares two concepts of man in thoughts of two great phenomenologists – Edith Stein and Roman Ingarden – connectedjoint not only by the intellectual bond but also by great friendship. The paper consists of two parts. First, the author presents Stein’s and Ingarden’s philosophy of man. Suchnotions as: subject, soul, spirit and body, experience, self-experience and activity of will, are shown from two perspectives. By analysing terminology used by both Stein and Ingardenin their works, the author tried to depict an appropriate – according to them –psychophysical constitution of man. While discussing Stein’s concepts, the author demonstratesalso her transition from phenomenology to mystical domain as well as her inspirationof Saint John of the Cross’ and Saint Theresa of Ávila’s works. Ingarden did notenter as firmly as Stein into the mystical domain, yet he opened a path into the Transcendenceby creating a concept of metaphysical qualities.